2015
DOI: 10.1186/s40164-016-0031-8
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of hydroxyurea use and clinical outcomes among patients with polycythemia vera in real-world clinical practice: a chart review

Abstract: BackgroundHydroxyurea (HU) is among the most commonly used cytoreductive treatments for polycythemia vera (PV), but previous research and clinical experience suggest that not all patients respond optimally, consistently, or durably to HU treatment. This study investigated patterns of HU use and impact on disease control among patients with PV in real-world clinical practice in the United States.MethodsOncologists and hematologists recruited between April and July 2014 reported data from patient charts. Treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 23 publications
3
15
0
1
Order By: Relevance
“…Indeed Parasuraman S in there serie of 1309 patients, the average age was 62.5 years. [23]. As against our results are relatively similar to those of the series of Mahjoub S. et al [22] in Tunisie who find a average age at 53 years in a cohort of 22 patients.…”
Section: Discussionsupporting
confidence: 93%
“…Indeed Parasuraman S in there serie of 1309 patients, the average age was 62.5 years. [23]. As against our results are relatively similar to those of the series of Mahjoub S. et al [22] in Tunisie who find a average age at 53 years in a cohort of 22 patients.…”
Section: Discussionsupporting
confidence: 93%
“…In HU‐treated patients, 81 patients (28.4%) had a hematocrit >45%, 88 patients (30.9%) had leukocyte counts >10 × 10 9 /L, and 97 patients (34%) had platelet counts >400 × 10 9 /L. An extensive recent study that provided data for 1080 HU‐treated patients reported rates similar to those in our study for hematocrit >45% (34.4%), but higher rates for platelet >400 × 10 9 /L (59.4%) and WBC >10 × 10 9 /L (58.2%) counts …”
Section: Discussionsupporting
confidence: 82%
“…First, eligible patients were hydroxyurea-resistant/intolerant; however, 59% in the BAT group continued hydroxyurea treatment [8] . This management approach was consistent with real-world practice before regulatory approval of ruxolitinib, in which some physicians continued hydroxyurea despite diminished benefit because of limited alternative treatment options [8,27] . Furthermore, in subgroup analyses by treatment type in the BAT arm, ruxolitinib was associated with greater clinical benefit at week 32 versus nonhydroxyurea treatment options for achievement of a ≥ 35% reduction from baseline in spleen volume (40 vs. 0%, respectively), hematocrit control without phlebotomy (60 vs. 16%) [8,25] , and a ≥ 50% improvement from baseline in MPN-SAF TSS (49 vs. 6%) [28] .…”
Section: Ruxolitinibmentioning
confidence: 80%